The Christological Dimension of Papal Ceremonies: Alexander VI and the Opening of the Holy Door - Lukasz Zak (Religions, 2025)
The aim of the paper will be to examine how Pope Alexander VI used liturgy to underscore his dignity as the vicar of Christ. During the pontificate of Rodrigo Borgia—and indeed throughout the 15th century—papal authority faced ongoing challenges, such as appeals to council, Savonarola’s preaching, and political conflicts with Charles VIII of France. In this context, the concept of the vicariate of Christ served as a crucial justification for the pope’s preeminent position within the Church. The unique bond between Christ and the pope was emphasized through various rites, including the opening of the Holy Door. In its first part, the paper will explore several examples of how Alexander VI portrayed himself as the vicar of Christ. This self-representation was conveyed not only through ceremonies, such as the possesso procession marking the inauguration of his pontificate, but also through artistic representations commissioned at various locations. Subsequently, the study will demonstrate that the opening of the Holy Door during the Jubilee of 1500 was carefully designed to highlight the Christological dimension of papal primacy. Although previous scholarship has addressed aspects of this rite, its political significance has largely been overlooked. By drawing on a variety of sources, this paper will trace the genesis and meaning of the ceremony, which was meticulously shaped by Alexander VI.